Comparison of Conventional and Modern Wound Care in Post-Section Wounds at Cut Mutia Hospital, North Aceh Regency in 2023 - Yusnidaryani, Yusnidaryani; Taufiq, Said; Fauzi, M. Jamil (Jurnal Health Sains, 2024)
The World Health Organization (WHO) sets the average cesarean sections (CS) standard at 5-15% per 1000 births. However, cesarean section rates in private hospitals exceed 30%, compared to 11% in government hospitals. This study investigates the prevalence and complications of surgical wound infections post-cesarean section and the effectiveness of modern wound dressing techniques in reducing these infections. Data analysis reveals cesarean wound infections occur during hospitalization (27%), re-admission (1%), and post-discharge (71%). Surgical wound infections (SWI) significantly increase morbidity, treatment duration, and healthcare costs, with a direct death rate ranging from 3% to 75% globally. The study evaluated modern wound dressings adhering to "moist wound healing" principles, such as hydrocolloids, alginate, and foam, which maintain a moist environment to enhance epithelial cell proliferation, accelerate wound healing, and reduce scarring. Findings indicate that moist wound dressings significantly improve healing outcomes, promoting epithelialization and collagen synthesis, with techniques showing a 30-50% increase in epithelialization and a 2-5 times faster re-epithelialization rate. These results highlight the need for adopting advanced wound care techniques to reduce surgical wound infections and improve patient recovery post-cesarean section. The study implies that healthcare providers should integrate modern wound care practices to enhance maternal health outcomes globally.